Penelitian Tindakan Konseling (PTBK): Meningkatkan Hubungan Sosial Melalui Layanan Klasik dengan Pendekatan Pembelajaran Berbasis Masalah untuk Siswa Kelas XI F3 - Sitorus, Sabar Halimah; Wastuti, Sri Ngayomi Yudha; Astuti, Sri (Yayasan Amanah Nur Aman, 2025)
This study aims to improve students' social relationships through classical guidance services using a Problem Based Learning (PBL) approach. The subjects were 29 students from class XI F3 at SMA Negeri 10 Medan, with 22 students identified as having difficulties in social interaction, such as low empathy, interpersonal conflict, and poor communication. This research employed the Guidance and Counseling Action Research (PTBK) model, implemented in two cycles. Each cycle consisted of planning, action, observation, and reflection stages. The findings indicated that the PBL-based classical guidance service was effective in enhancing students' social relationships. This was evidenced by the increase in average questionnaire scores from 62.06% (moderate category) in the pre-cycle, to 77.93% (high category) in the first cycle, and reaching 87.93% (very high category) in the second cycle. The PBL approach encouraged students to analyze real social problems, reflect empathetically, and develop collaborative problem-solving skills. Therefore, classical guidance with a PBL approach can be recommended as an effective strategy for improving social skills in high school students.